Charismatic Leadership, Compensation, and Individual Characteristics on Employee Performance by Intervening Job Satisfaction - Eko Pristiwanto; Sumartik Sumartik; Vera Firdaus (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
The main objective of this study is to evaluate the effect of salary, charismatic leadership style, and individual attributes on employee performance, considering the mediating role of job satisfaction. The main data source of this study is a questionnaire, which is a descriptive quantitative approach. Furthermore, the Partial Least Square (PLS) technique can analyze the collected data through Smart PLS 3 software. This study involved Juke Abadi Sidoarjo employees who were not managers. The total sample method was used to select a sample of 60 respondents. The results showed that compensation has a significant impact on performance. The relationship between compensation and employee satisfaction is also statistically significant. The impact of charismatic leadership style on employee performance can be influenced by job satisfaction. The impact of individual traits on performance is substantial, and also influencing job satisfaction. The performance of employees is influenced by individual traits that are mediated through work satisfaction.